Sistem Pakar Untuk Diagnosa Hama Tanaman Padi Berbasis Android - Sujarwo, Anton, Dedi Gunawan, S.T., M.Sc (2016)
The rice is a producer of the human needs of a very important its existence. But often the result obtained are not optimal caused of diseases and pests. All it attack the rice by leaving the symptoms that can be seen. A lot of farmers still using the manual method to find a pests, which is by see directly in the field and creating scarecrow. In fact, to know the diseases of rice plants, we have to see the symptoms of diseases. And then, to do it all would need the knowledge more about rice plants. The farmers often too late to find the symptoms caused of less knowledge about rice plants. An important stage is to prevent the spread of the symptoms before it is getting worst. All of it can be resolved by the artificial intelligence called expert system. It created to detected the diseases and pests of ricebased on the symptoms. The expert system is using the forward chaining method and it implemented on a smartphone. The result of expert system that have been successfully displays information about diseases and pests, displays the diagnose result along with the solution based on the symptoms that have been selected by user, and explanations about the symptoms that can be understand by general people.